2009
DOI: 10.1002/hlca.200900270
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Genetic Study of Ligularia cyathiceps in Yunnan Province of China

Abstract: Dedicated to Professor Emeritus Takeyoshi Takahashi on the occasion of his 83rd birthdayRoot chemicals and evolutionarily neutral DNA regions in L. cyathiceps samples collected in the Zhongdian (Shangrila) County of Yunnan, P. R. China, were examined. Twenty compounds were isolated, including three new ones, 1b,10b-epoxy-6b-(propionyloxy)furanoeremophilan-9-one (6), 1b,10b-epoxy-8a-ethoxyeremophila-6,11-diene (14), and 11aH-6b-isobutyryloxy-1b,10b,7b,8b-diepoxyeremophilan-12,8a-olide (15). The chemical diversi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
37
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…We are interested in biologically active terpenoids from Asteraceae plants and have studied the chemical constituents of Ligularia, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Saussurea, 22,23) Cremanthodium, [24][25][26][27] and Eupatorium. [28][29][30][31] In our previous study on E. glehnii growing in Japan, especially in Obihiro (Hokkaido), Fujimi-cho (Nagano), and Tokushima, a large diversity in the chemical constituents was found, while there was no diversity in DNA sequences (atpB-rbcL intergenic region).…”
mentioning
confidence: 99%
“…We are interested in biologically active terpenoids from Asteraceae plants and have studied the chemical constituents of Ligularia, [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] Saussurea, 22,23) Cremanthodium, [24][25][26][27] and Eupatorium. [28][29][30][31] In our previous study on E. glehnii growing in Japan, especially in Obihiro (Hokkaido), Fujimi-cho (Nagano), and Tokushima, a large diversity in the chemical constituents was found, while there was no diversity in DNA sequences (atpB-rbcL intergenic region).…”
mentioning
confidence: 99%
“…8 and Ligularia cyathiceps Hand.-Mazz. 6 The production of these compounds represents one of the major lineages among furanoeremophilane-producing species.…”
Section: Resultsmentioning
confidence: 99%
“…c ) DQ272328. In contrast, 9-oxofuranoeremophilanes 1 -3 are characteristic of L. cyathiceps [9] and have not been found in L. subspicata. e ) Two sequences with and without an A were present.…”
mentioning
confidence: 84%
“…The major diagnostic difference between the two species is the presence (L. lamarum) or the lack (L. subspicata) of ligulate florets. L. cyathiceps produces cacalol as the major component of the root chemicals [9]. In addition, we have found that L. subspicata and L. lamarum are indistinguishable in terms of both the chemical composition in the root and the nucleotide sequence of the internal transcribed spacers (ITSs) of the ribosomal RNA gene cluster [14] [15].…”
mentioning
confidence: 92%
See 1 more Smart Citation